EPIDEMIOLOGY AND COMORBIDITIES IN BULLOUS PEMPHIGOID IN THE PERIOD FROM JANUARY OF 2019. TO THE JANUARY OF 2021. - Radičević, Miloš; Minić, Snežana (Medicinski podmladak, 2022)
Introduction: Bullous pemphigoid is an autoimmune bullous dermatosis that most commonly occurs in elderly patients. Bullous pemphigoid due to its pathogenesis and treatment of the disease can also affect the development of comorbidities.Aim: Determination of comorbidities and their frequency in patients with bullous pemphigoid as well as their distribution by sex and to estimate the duration of dermatosis from the onset of symptoms to data collection.Material and methods: In the period from January 2019 to January 2021, 80 patients were analyzed. Basic patient data (age, sex, time of illness) and data on accompanying comorbidities were obtained. Data were categorized based on the ICD-10 classification into groups of diseases as well as individual diseases that occurred frequently in the population.Results: Of the total number of respondents, 41.3% were male and 58.8% female. The average age of the respondents was 75.8 years, 76.45 years for men and 75.36 years for women. The period from the onset of symptoms to data collection was 3 months, while the average age of the disease in all subjects was 74.4 years. The most common comorbidities were hypertension 73.75%, psychiatric diseases 25%, type 2 diabetes mellitus 25%, other skin diseases 21.25%, urinary tract disorders 18.75%, ischemic heart disease 12, 5%, type 1 diabetes mellitus 10%, kidney disease 8.75%, neurological disease 6.25%. Comorbidities were statistically more common in female patients: hypertension, ischemic heart disease, skin diseases and type 2 diabetes mellitus.Conclusion: In our study, we confirmed that bullous pemphigoid is a disease of the elderly, predominatly female. Female patients suffer from some comorbidities more often. The period from the onset of symptoms to the collection of data is about 3 months. We also showed that there are a number of comorbidities in the studied pemphigoid population, however, a large number of studies are needed to determine their association.
Keywords: Bullous pemphigoid; comorbidities; older age